Producción de plántulas de Ochroma pyramidale (Cay. ex Lam.) Urb. (balsa) y Tectona grandis L.f. (teca) a nivel de vivero con sustratos de carbón activado provenientes de residuos de cosechas agrícolas y forestales - Rodríguez Estrada, Ángel Fabricio (2021)
The production of excellent quality seedlings in O. pyramidale and T. grandis has led to research being carried out to determine the ideal substrate for their propagation, for which different materials have been used and activated carbon is currently being considered as a means of propagation in vegetables, for which the present study aimed to evaluate the production of O. pyramidale and T. grandis seedlings at the nursery level with activated carbon substrates from agricultural and forestry harvest residues. The substrates used were T1 (activated carbon from rice husk + plantation land); T2 (activated carbon from banana rachis + plantation land); T3 (wood activated carbon + plantation land); T0 (control). A completely randomized design was used with 3 treatments and 3 repetitions respectively. The variables on germination start day (DIG) were determined; day of maximum germination (DMG); final day of germination (DFG); germination percentage (PG), mortality percentage (PM); seedling height (AP); stem diameter (DT); number of sheets (NH); Final shift survival percentage (PS), the Tukey test was applied at 5% to find significant differences between the substrates. The best averages in O. pyramidale were obtained in T1 with 100% germination and 0% mortality, height of 6.84 cm, diameter of 3 mm, 6 leaves and a survival of 97%, for T. grandis on T1 presented 87% germination and 13% mortality, height of 5.56 cm, diameter of 2 mm, 6 leaves and survival of 92%. Keywords: germination, morphological variables, survival, Tukey's test, waste